Community Perceptions on Malaria and Care-Seeking Practices in Endemic Indian Settings : Policy Implications for the Malaria Control Programme - Das, Ashis; Das Gupta, R.K.; Friedman, Jed; Pradhan, Madan M.; Mohapatra, Charu C. (BioMed Central, 2015)
The focus of India’s National Malaria Programme witnessed a paradigm shift recently from health facility to community-based approaches. The current thrust is on diagnosing and treating malaria by community health workers and prevention through free provision of long-lasting insecticidal nets. However, appropriate community awareness and practice are inevitable for the effectiveness of such efforts. In this context, the study assessed community perceptions and practice on malaria and similar febrile illnesses. This evidence base is intended to direct the roll-out of the new strategies and improve community acceptance and utilization of services.